Learning Curve for Flow Diversion of Posterior Circulation Aneurysms: A Long-Term International Multicenter Cohort Study - Adeeb, N.; Dibas, Mahmoud; Griessenauer, C. J.; Cuellar, H. H.; Salem, M. M.; Xiang, S.; Enriquez-Marulanda, A.; Hong, T.; Zhang, H.; Taussky, P.; Grandhi, R.; Waqas, M.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Flow diversion has gradually become a standard treatment for intracranial aneurysms of the anterior circulation. Recently, the off-label use of the flow diverters to treat posterior circulation aneurysms has also increased despite initial concerns of rupture and the suboptimal results. This study aimed to explore the change in complication rates and treatment outcomes across time for posterior circulation aneurysms treated using flow diversion and to further evaluate the mechanisms and variables that could potentially explain the change and outcomes. MATERIALS AND METHODS: A retrospective review using a standardized data set at multiple international academic institutions was performed to identify patients with ruptured and unruptured posterior circulation aneurysms treated with flow diversion during a decade spanning January 2011 to January 2020. This period was then categorized into 4 intervals. RESULTS: A total of 378 procedures were performed during the study period. Across time, there was an increasing tendency to treat more vertebral artery and fewer large vertebrobasilar aneurysms (P = .05). Moreover, interventionalists have been increasingly using fewer overlapping flow diverters per aneurysm (P = .07). There was a trend toward a decrease in the rate of thromboembolic complications from 15.8% in 2011?13 to 8.9% in 2018?19 (P = .34).CONCLUSIONS: This multicenter experience revealed a trend toward treating fewer basilar aneurysms, smaller aneurysms, and increased usage of a single flow diverter, leading to a decrease in the rate of thromboembolic and hemorrhagic complications.
CRIS-Team WoS Importer:2022-10-28